Pengembangan Produk Stik Sawi: Pemberdayaan Masyarakat Desa Persiapan Nyama Kabupaten Maluku Barat Daya - Edy Sony; Urbanus Maulekilela; Honorios De Gustino Luturyali; Belince Makatita; Paula Ifana Tamneha; Elen Lotkery; Evadora Wuarlela; Siska Knyarpilta; Leliana Lekiwona; Jekson Meikudy; Natalia Philipus; Lelpint Wakole; Fifian Ifasaksisly; Penina Knyarilay; Asince Petrus (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
This community service aims to empower the Dasawisma Women's Group of Nyama Preparation Village, Maluku Barat Daya Regency, through training in making mustard sticks as a product innovation based on local agricultural products. The problems faced are the low utilisation of mustard harvest which leads to low selling prices and limited product innovation skills. The method used was a participatory approach with hands-on experience-based training techniques. The training includes the process of making mustard sticks, starting from the selection of ingredients, processing, to product packaging. The results showed that the Dasawisma women's group succeeded in improving their skills in processing mustard into value-added products. The emergence of local leaders and the creation of solidarity between group members are also positive impacts of this training. The programme provided new economic opportunities for the group, as well as introducing mustard stick products to the local market. In conclusion, this service successfully empowered the community through local product innovation and formed a new working structure that is more organised and sustainable.